2018
DOI: 10.1007/s00787-018-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific trajectories of ADHD symptoms from adolescence to young adulthood

Abstract: Reports of current ADHD symptoms in adults with a childhood diagnosis of ADHD are often discrepant: While one subgroup reports a particularly high level of current ADHD symptoms, another reports-in contrast-a very low level. The reasons for this difference remain unclear. Although sex might play a moderating role, it has not yet been examined in this regard. In an epidemiological cohort study from birth to young adulthood, childhood ADHD diagnoses were assessed at the ages of 4.5, 8, and 11 years based on pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
1
18
1
1
Order By: Relevance
“…Moreover, the presentation of ADHD may differ between the sexes, with impulsivity more often diagnosed in boys [3]; however, other studies have reported similar presentation of ADHD symptoms between the sexes [4][5][6]. Further, adult women with ADHD have more severe symptoms if they were diagnosed with ADHD as a child, while this relationship is not present in boys [7]. The incidence of schizophrenia is higher in males [8], and may be slightly more prevalent in men [9], and the initial presentation is different by sex, with onset typically seen later in females [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the presentation of ADHD may differ between the sexes, with impulsivity more often diagnosed in boys [3]; however, other studies have reported similar presentation of ADHD symptoms between the sexes [4][5][6]. Further, adult women with ADHD have more severe symptoms if they were diagnosed with ADHD as a child, while this relationship is not present in boys [7]. The incidence of schizophrenia is higher in males [8], and may be slightly more prevalent in men [9], and the initial presentation is different by sex, with onset typically seen later in females [10,11].…”
Section: Introductionmentioning
confidence: 98%
“…By contrast, clinical studies typically report a greater prevalence of combined-type ADHD [ 5 , 12 , 22 ]. Early meta-analyses of gender effects have found lower severity of hyperactivity-impulsivity [ 40 ], or all ADHD symptoms (inattention, hyperactivity, impulsivity) [ 24 ] in girls than boys, although individual studies show more mixed results [ 8 , 35 , 41 , 42 ].…”
Section: Results and Consensus Outcomementioning
confidence: 99%
“…People may experience and respond to the same behaviour of males and females in different ways due to gender-related behavioural expectations [ 42 ]. For example in two studies where teachers were presented with ADHD-like vignettes, when simply varying the child’s name and pronouns used from male to female, boys names were more likely to be referred for additional support [ 45 ] and considered more suitable for treatment [ 46 ].…”
Section: Results and Consensus Outcomementioning
confidence: 99%
“…Hinsichtlich der Entwicklung externalisierender Störungen über die Lebensspanne sprechen die Befunde geschlechtsbedingt für einen homotypischen Verlauf: So prädizieren externalisierende Diagnosen in der Kindheit nur bei weiblichen Teilnehmern auch ADHS im jungen Erwachsenenalter [ 27 ].…”
Section: Erkenntnisse Aus Exemplarischen Kohortenstudienunclassified